Aberración cromática en el Cardenal Común (Paroaria coronata) en Paraguay - Etchegaray, Alan Martin; Benítez Riveros, Camilo; Galluppi Selich, Tatiana; Irala Melgarejo, Rebeca; Rojas Barrios, Silvana; Ruíz López, Rodolfo (Nuestras Aves, 2016)
Este artículo no cuenta con un resumen.